2018
DOI: 10.26442/terarkh201890360-66
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cell Therapy for Perianal Crohn’s Disease

Abstract: Aim. To compare the effectiveness of the effect of combination therapy (local and systemic administration) with bone marrow mesenchymal stromal cells (MSC), anticlitokine therapy with infliximab (IFX), and antibiotic (AB)/immunosuppressive (IS) therapy on the frequency of healing of simple perianal fistulas in Crohn's disease. Materials and methods. In our study, the 1-st group of patients aged 19 to 58 years (Me-29) (n = 12) received MSCs culture systemically according to the scheme and locally. The 2-nd grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…They demonstrated that combined cell and anti-cytokine therapy with CZP of CD with perianal lesions promotes more frequent and prolonged closure of simple fistulas, compared with BSCs monotherapy and CZP monotherapy. Knyazev et al [ 67 ] performed a clinical trial to compare the effectiveness of combination therapy with BSCs, anticytokine therapy with infliximab (IFX), and antibiotic/immunosuppressive therapy in CD fistulas. They demonstrated that combined cellular and anticytokine therapy of CD with perianal lesions significantly contributes to the more frequent and prolonged closure of simple fistulas, as compared to antibiotics/immunosuppressors, and to a decrease in the frequency of recurrence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that combined cell and anti-cytokine therapy with CZP of CD with perianal lesions promotes more frequent and prolonged closure of simple fistulas, compared with BSCs monotherapy and CZP monotherapy. Knyazev et al [ 67 ] performed a clinical trial to compare the effectiveness of combination therapy with BSCs, anticytokine therapy with infliximab (IFX), and antibiotic/immunosuppressive therapy in CD fistulas. They demonstrated that combined cellular and anticytokine therapy of CD with perianal lesions significantly contributes to the more frequent and prolonged closure of simple fistulas, as compared to antibiotics/immunosuppressors, and to a decrease in the frequency of recurrence of the disease.…”
Section: Discussionmentioning
confidence: 99%
“… At 1-year, healing of 58.3% (7/12) in group 1, 60% (6/10) in group 2, and 14.3% (2/14) in group 3. [ 189 ] Herreros M. D. 2019, Spain I/II CD (18 with perianal CD) 45 Auto-ASCs allo-ASCs Local / IV Nothing >6 month 55.5% of CD patients achieved healing (absence of suppuration). CD patients receiving SVF, auto-ASCs and allo-ASCs were cured by 40%, 66.6% and 55.5% respectively.…”
Section: Therapeutic Effects Of Scs In Ibdmentioning
confidence: 99%
“…Продемонстрированы возможность, безопасность и эффективность применения костномозговых МСК банка МРНЦ при язвенном колите и болезни Крона [13]. Установлено, что комбинированная клеточная и антицитокиновая терапия болезни Крона с перианальными поражениями достоверно способствует более частому и длительному закрытию простых свищей по сравнению с антибиотиками/иммуносупрессорами [14,15]. Кроме того показано, что трансплантация МСК способствует поддержанию более длительной клинической ремиссии у больных с люминальной формой болезни Крона по сравнению с группой больных, страдающих язвенным колитом [16,17] ных клеток на эффективность репарации кроветворения при использовании сублетальных доз циклофосфана [18].…”
unclassified